2022
DOI: 10.1177/15593258221078392
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Early-Stage Alzheimer’s Disease With CT Scans of the Brain: A Case Report

Abstract: We report the case of a patient in Massachusetts with early-stage Alzheimer’s disease who was treated with low doses of ionizing radiation to the brain. He requested this treatment after reading about a patient with severe Alzheimer’s in Michigan who improved remarkably after receiving 4 CT scans. After his first treatment in April 2016, mental clarity improved. His impaired conversation, reading, and sense of humor were restored, especially his virtuosic clarinet jazz-playing. However, executive function rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…This was the case with our patient, with the HBOT being started at an earlier age and in the earlier course of his cognitive deterioration, alongside the recommended antidementia treatment, and was maintained with prolong-term and regular HBOT intervention over a period of several years. A previous study reported a sustained HBOT benefit of one month in AD, and up to 6 months in amnestic MCI following only one course of HBOT [36]. Interestingly, prolonged HBOT sessions (43 in total) in an older patient with more advanced AD stage who was not on antidementia drugs but 'treated' with 6 CT brain scan sessions did not show these benefits [37].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This was the case with our patient, with the HBOT being started at an earlier age and in the earlier course of his cognitive deterioration, alongside the recommended antidementia treatment, and was maintained with prolong-term and regular HBOT intervention over a period of several years. A previous study reported a sustained HBOT benefit of one month in AD, and up to 6 months in amnestic MCI following only one course of HBOT [36]. Interestingly, prolonged HBOT sessions (43 in total) in an older patient with more advanced AD stage who was not on antidementia drugs but 'treated' with 6 CT brain scan sessions did not show these benefits [37].…”
Section: Discussionmentioning
confidence: 90%
“…The heterogeneity of reported clinical assessments and outcomes in case reports [29,34,37] and small studies [19,36], outcome measures and time recorded as well as the variability of reported HBOT protocols [40], makes it difficult to comment about the HBOT therapeutic impact in AD. The studies to date have indicated that one course of HBOT only temporarily ameliorates cognitive impairment in AD patients [36] and the effects may not be permanent. Furthermore, only one aspect of the AD clinical symptoms, cognitive performance, seems to have been addressed, but not the accompanying neuropsychiatric changes and/or quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…After receiving four CT scans, the patient's mental clarity improved and even exhibited restored function of clarinet jazz-playing. The treatment was discontinued due to fears of adverse events however, further research is needed to assess if CT scans could serve a role in temporarily improving the quality of life of patients with AD in the future (Cuttler et al, 2022;Jebelli et al, 2022).…”
Section: Computed Tomographymentioning
confidence: 99%
“…Similarly, a low dose of 100 mGy caused the downregulation of neural pathways associated with cognitive dysfunctions in normal human aging and Alzheimer's disease [99]. Recently, there were reports on individual cases of Alzheimer's that showed significant recovery of their cognitive and their intellectual capacities after low (40-80 mGy) or even higher doses of IR [100][101][102]. It is thought that these beneficial effects of low-dose IR are due to an adaptive response mobilizing cellular defense and signaling systems (antioxidants, etc.).…”
Section: Hormesismentioning
confidence: 99%